2022
DOI: 10.52711/0974-360x.2022.00179
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole: A Re-emerging choice for Oral candidiasis in patients with human immunodeficiency virus infection/acquired Immunodeficiency Syndrome

Abstract: Background: The long term use of antifungals for oral candidiasis (OC) in patients with Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) causes some strains to be resistant to certain antifungals. HIV/AIDS are currently most common in men. Aim: To evaluate ketoconazole sensitivity on Candida species in male HIV/AIDS patients with OC. Method: This is an observational descriptive study at the Outpatient Unit and Inpatient Installation of the Infectious Disease Intermediate Care U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This also will guide in choosing the empiric or prophylactic drug before the antifungal resistance test result is available. [16][17][18][19][20] In conclusion, plants with medicinal properties are considered to be important source of novel potentially therapeutic compounds. The present study has shown the antimycotic activity of rosemary oil on Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…This also will guide in choosing the empiric or prophylactic drug before the antifungal resistance test result is available. [16][17][18][19][20] In conclusion, plants with medicinal properties are considered to be important source of novel potentially therapeutic compounds. The present study has shown the antimycotic activity of rosemary oil on Candida species.…”
Section: Discussionmentioning
confidence: 99%